Inżynieria oprogramowania w projektach grupowych - Pławiak-Mowna, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book describes experiments on realisation of team-based student projects in relation to their form, organisation and execution with partners from the IT field. Additionally, elements concering teamwork in affiliation with some parts of the process of creating software are present. It discusses the process of aquiring teamwork skills, based on long-term expertise and experiments.
Keywords: projekt grupowy; studenckie zespoły; kształcenie metodą projektów; projekt informatyczny; group project; student group work; project-based learning; IT project